2009
DOI: 10.1002/chem.200901249
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Cyclic Trisilanes: “Spring‐Loaded” Precursors to Methylphenylsilylene

Abstract: Two new cyclic trisilanes containing a SiMePh moiety in the central position have been synthesized, and their photochemistries studied by steady-state and laser flash photolysis methods. The yield of the transient silylene SiMePh increases at the expense of that of the corresponding cyclic silene derivative (formed by photochemical 1,3-silyl migration into the phenyl ring) as the ring size is decreased from 7 to 6, facilitating the direct detection of the silylene by laser flash photolysis. The UV/Vis spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Transient silylenes have been characterized using UV–vis and infrared spectroscopy in frozen matrices, and in the gas phase and fluid solution by time-resolved UV–vis spectrophotometry, or flash photolysis. This has allowed the direct detection and characterization of the simplest carbon-substituted silylenes in solution, including SiMe 2 , − , SiPh 2 , SiMePh, and SiMes 2 (Mes = 2,4,6-trimethylphenyl), using oligosilanes such as 2 – 4 as photoprecursors.…”
Section: Introductionsupporting
confidence: 85%
“…Transient silylenes have been characterized using UV–vis and infrared spectroscopy in frozen matrices, and in the gas phase and fluid solution by time-resolved UV–vis spectrophotometry, or flash photolysis. This has allowed the direct detection and characterization of the simplest carbon-substituted silylenes in solution, including SiMe 2 , − , SiPh 2 , SiMePh, and SiMes 2 (Mes = 2,4,6-trimethylphenyl), using oligosilanes such as 2 – 4 as photoprecursors.…”
Section: Introductionsupporting
confidence: 85%
“…The photochemistry of catenated group 14 compounds is of interest since this method can be used to convert one type of catenate to another and also can be used for the generation of reactive intermediates including silylenes, germylenes, stannylenes, and group 14 element centered radical species that can be trapped and characterized . In the case of germanium, the photochemistry of the cyclotrigermane (Mes 2 Ge) 3 has been the most extensively studied and it has been shown that this compound is photochemically converted to a germylene Mes 2 Ge : and a digermene Mes 2 Ge=GeMes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Silylenes are important intermediates in silicon hydride and organosilicon chemistry. Their characteristic reactions include insertions into Si–H, Si–OR, and O–H bonds and π-type additions across CC and CC bonds. Many of the fine details of the mechanisms of these reactions have been revealed by time-resolved kinetics studies employing direct monitoring of silylenes. In recent times, much attention has been devoted to the preparation and properties of large silylenes, stabilized either by bulky substituents, or by being built into N-heterocyclic rings or with N-heterocyclic adducts. Nevertheless there still remains a need to uncover further details of the behavior of the smaller, more reactive silylenes to establish a reactivity baseline.…”
Section: Introductionmentioning
confidence: 99%